2009
DOI: 10.1037/a0016368
|View full text |Cite
|
Sign up to set email alerts
|

Component structure of individual differences in true and false recognition of faces.

Abstract: Principal-component analyses of 4 face-recognition studies uncovered 2 independent components. The first component was strongly related to false-alarm errors with new faces as well as to facial "conjunctions" that recombine features of previously studied faces. The second component was strongly related to hits as well as to the conjunction/new difference in false-alarm errors. The pattern of loadings on both components was impressively invariant across the experiments, which differed in age range of participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 90 publications
(168 reference statements)
6
33
0
1
Order By: Relevance
“…Age invariance in associative memory would thus depend on how much memory performance can rely on familiarity, as also suggested by the preserved ability of older adults to discriminate between studied and unstudied intra-facial combinations in a task demonstrated as being familiarity-dependent (Bartlett, Shastri, Abdi, & Neville-Smith, 2009; Edmonds et al, 2012). In contrast, when item and color were encoded as separate components, source retrieval depends more heavily on recollection.…”
Section: Discussionmentioning
confidence: 99%
“…Age invariance in associative memory would thus depend on how much memory performance can rely on familiarity, as also suggested by the preserved ability of older adults to discriminate between studied and unstudied intra-facial combinations in a task demonstrated as being familiarity-dependent (Bartlett, Shastri, Abdi, & Neville-Smith, 2009; Edmonds et al, 2012). In contrast, when item and color were encoded as separate components, source retrieval depends more heavily on recollection.…”
Section: Discussionmentioning
confidence: 99%
“…If there is a match, a feeling of familiarity will arise. Here, the framework posits that familiarity and recollection can be separated (e.g., Bartlett et al, 2009 ; Edmonds et al, 2012 ) in the final decision process. Recognition based on feelings of familiarity does not require the retrieval of additional information regarding the person the face belongs to, the context under which the face was previously encountered, etc.…”
Section: Organizing Frameworkmentioning
confidence: 99%
“…Finally, we note that the neuropsychological model postulating separate temporal lobe and frontal lobe contributions to face memory (Fig. 4) has received indirect support from recent studies of face recognition in normal subjects that used principal component analyses to identify two independent components: one serving to increase hits (temporal lobe memory) and the other to reduce false alarms (frontal executive) [5].…”
Section: Discussionmentioning
confidence: 94%
“…Similar to the neuropsychological explanations offered to account for memory distortions in frontal patients, false facial recognition in older individuals has been attributed to an age-related deficit in context recollection and a corresponding increase in the use of familiarity when making face memory decisions [1,3,47,64,74]. Furthermore, it has been suggested that the context-recollection deficit responsible for the increased susceptibility of older adults to face memory illusions reflected an age-related decline in frontal lobe function [5,18,64]. This theoretical formulation is consistent with other evidence that automatic memory processes such as familiarity remain relatively invariant with age while more controlled memory processes such as recollection and source monitoring show agerelated decline [28,30,33,76,83], and also with neuroimaging studies demonstrating prominent changes in frontal lobe structural/functional integrity with increasing age [8,15,27,78].…”
Section: Face Memory Distortions In Cognitively Intact Older Adultsmentioning
confidence: 84%
See 1 more Smart Citation